Table of Content - - (Journal of natural sciences, life and applied sciences, 2023)
Table of Content:1. Monitoring Urban Expansion in Urban Abha Using Remote Sensing and Geographic Information Systems (1984 - 2020)Mr. Saad Abdullah Al Omeir , Co-Prof. Ibrahim Obaid Alshwesh2. Flow duration curve a tool to characterize, analyze and management low water in a Semi-Arid context: case of the Tassaout watershed upstream of the Moulay Youssef dam (1978-2016), Central High Atlas, MoroccoDr. CHAKIR Mohamed , Dr. El-GHACHI Mohamed , Dr. GHADBANE Omar , Dr. OUAKHIR Hassan3. Use Spatial Analysis Tools in A Study The Hydromorphological Characteristics of Wadi Al-Rimah in Its Lower Section in Qassim AreaMrs. Maha Awwad Alenziy, Prof. Ahmed Abdullah Aldughairi4. Trends in annual rainfall amounts at Jeddah and Al-Wajh stations in the Kingdom of Saudi Arabia for the years (1987-2016 AD)Lecturer \ Jamila Awadh Alanazy5. Integrated environmental management of solid medical waste in medical facilities in the Capital Secretariat of Sana'a as a case studyMr. Khaled Hussein Abduallah Tahish, Prof. Abdulwaly Mohsen Mohsen Al-Arashiy , Prof. Mohamed Ahmed Hamoud Maiyas6. Assessment of Jeddah City Public Health Facilities Readiness to Combat EpidemicsMr. Serajaddin Omar Daghestani, Dr. Faisal Mohammed Jamalallail
Keywords: Journal of Natural Sciences, Life and Applied Sciences